Mitigating Cardiotoxicity of Dendrimers: Angiotensin-(1-7) via Its Mas Receptor Ameliorates PAMAM-Induced Cardiac Dysfunction in the Isolated Mammalian Heart - Saghir Akhtar; Fawzi Babiker; Usman A. Akhtar; Ibrahim F. Benter (MDPI AG, 2022)
Aim: The influence of the physiochemical properties of dendrimer nanoparticles on cardiac contractility and hemodynamics are not known. Herein, we investigated (a) the effect of polyamidoamine (PAMAM) dendrimer generation (G7, G6, G5, G4 and G3) and surface chemistry (-NH2, -COOH and -OH) on cardiac function in mammalian hearts following ischemia-reperfusion (I/R) injury, and (b) determined if any PAMAM-induced cardiotoxicity could be mitigated by Angiotensin-(1-7) (Ang-(1-7), a cardioprotective agent. Methods: Hearts isolated from male Wistar rats underwent regional I/R and/or treatment with different PAMAM dendrimers, Ang-(1-7) or its MAS receptors antagonists. Thirty minutes of regional ischemia through ligation of the left anterior descending coronary artery was followed by 30 min of reperfusion. All treatments were initiated 5 min prior to reperfusion and maintained during the first 10 min of reperfusion. Cardiac function parameters for left ventricular contractility, hemodynamics and vascular dynamics data were acquired digitally, whereas cardiac enzymes and infarct size were used as measures of cardiac injury. Results: Treatment of isolated hearts with increasing doses of G7 PAMAM dendrimer progressively exacerbated recovery of cardiac contractility and hemodynamic parameters post-I/R injury. Impairment of cardiac function was progressively less on decreasing dendrimer generation with G3 exhibiting little or no cardiotoxicity. Cationic PAMAMs (-NH2) were more toxic than anionic (-COOH), with neutral PAMAMs (-OH) exhibiting the least cardiotoxicity. Cationic G7 PAMAM-induced cardiac dysfunction was significantly reversed by Ang-(1-7) administration. These cardioprotective effects of Ang-(1-7) were significantly revoked by administration of the MAS receptor antagonists, A779 and D-Pro7-Ang-(1-7). Conclusions: PAMAM dendrimers can impair the recovery of hearts from I/R injury in a dose-, dendrimer-generation-(size) and surface-charge dependent manner. Importantly, PAMAM-induced cardiotoxicity could be mitigated by Ang-(1-7) acting through its MAS receptor. Thus, this study highlights the activation of Ang-(1-7)/Mas receptor axis as a novel strategy to overcome dendrimer-induced cardiotoxicity.